-2x+10=3x+45

Simple and best practice solution for -2x+10=3x+45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+10=3x+45 equation:


Simplifying
-2x + 10 = 3x + 45

Reorder the terms:
10 + -2x = 3x + 45

Reorder the terms:
10 + -2x = 45 + 3x

Solving
10 + -2x = 45 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
10 + -2x + -3x = 45 + 3x + -3x

Combine like terms: -2x + -3x = -5x
10 + -5x = 45 + 3x + -3x

Combine like terms: 3x + -3x = 0
10 + -5x = 45 + 0
10 + -5x = 45

Add '-10' to each side of the equation.
10 + -10 + -5x = 45 + -10

Combine like terms: 10 + -10 = 0
0 + -5x = 45 + -10
-5x = 45 + -10

Combine like terms: 45 + -10 = 35
-5x = 35

Divide each side by '-5'.
x = -7

Simplifying
x = -7

See similar equations:

| -2*25+2y=44 | | c/4=1`6 | | 0.03(y-7)+0.14y=0.07y-0.20 | | 9x(2x-4)= | | 3x-9y=-21 | | 13=1-13 | | 27x+14=3(9x-7) | | 2e-8=14# | | -5(6x-4)= | | 6f=-5x+2 | | Y-5x=-8 | | 2x^2+5=-32 | | (-35)x(-14)x(0.5)= | | -81-4(7-3x)=13(x-8) | | 84-48/8 | | .25t+9=3 | | 2x-10x=30 | | (4x-9)(10x+5)=0 | | f(x)=-5x^2+2x-1 | | x^2-4x/x | | 2*-10-9y=38 | | 46-1+8x=18x-15 | | 6n-3-9n=4+2n-8 | | 28-3c+4=2c+6+1c | | 18/5-2k=6 | | 11x-7=7+9a | | 4(2p-8)-6p=20-4(p+6) | | 28-3c+4=2c+6+c | | 2a+4=6a+8 | | ln(4)+ln(20)=0 | | -7x+9=-2x-21 | | 11-x+4=3x+5-8x |

Equations solver categories